2022
DOI: 10.1177/20503121221135486
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of contraceptive implant discontinuation among women who used implant in Ethiopia: Systemic review and meta-analysis

Abstract: The likelihood of contraceptive implant discontinuation is very common and varies worldwide. This high prevalence of discontinuation may also indicate problems with implementation of family planning programmes. Consequently, a significant number of women are exposed to conception after discontinuation. Although studies have been conducted in Ethiopia, there are inconsistencies across studies. Therefore, this meta-analysis aimed to estimate the pooled prevalence of contraceptive implant discontinuation among wo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 33 publications
0
3
0
Order By: Relevance
“…Studies from different parts of Ethiopia also show that implanon discontinuation remains high, ranging from 16% in Tigray Region [ 14 ] to 65% in Debre Tabor City [ 15 ]. The most recent review from Ethiopia also reported that the pooled prevalence of implant discontinuation was 36.95% [ 16 ].…”
Section: Introductionmentioning
confidence: 99%
“…Studies from different parts of Ethiopia also show that implanon discontinuation remains high, ranging from 16% in Tigray Region [ 14 ] to 65% in Debre Tabor City [ 15 ]. The most recent review from Ethiopia also reported that the pooled prevalence of implant discontinuation was 36.95% [ 16 ].…”
Section: Introductionmentioning
confidence: 99%
“… 2 This safe and cost-effective contraception method offers women reliable contraception with a clinical success rate greater than 99% for up to 3–5 years. 3 5 Although contraceptive implant use was previously low in Thailand, it is continuously increasing. According to the National Statistical Office of Thailand, contraceptive implants accounted for 0.4% of contraceptive methods among married women aged 15–49 years in 2009, 6 which increased to 1.6% in 2019.…”
Section: Introductionmentioning
confidence: 99%
“…Early discontinuation of contraceptive implants has been widely reported worldwide, which could put women at risk of negative health consequences. 3 , 4 , 9 , 10 Unscheduled menstruation, prolonged bleeding or spotting, and other undesirable side effects, which can be managed successfully with over-the-counter medicine, 11 have been reported as a common cause for early discontinuation. 9 According to the US practice recommendations, insertion should be performed by trained healthcare professionals, with clear consultation regarding the possible adverse reactions and complications of the insertion procedure.…”
Section: Introductionmentioning
confidence: 99%